The Bacterial Communities of Little Cigars and Cigarillos Are Dynamic Over Time and Varying Storage Conditions - Smyth, Eoghan M.; Chattopadhyay, Suhana; Babik, Kelsey; Reid, Molly; Chopyk, Jessica; Malayil, Leena; Kulkarni, Prachi; Hittle, Lauren E.; Clark, Pamela I.; Sapkota, Amy R.; Mongodin, Emmanuel F. (Frontiers in Microbiology, 2019)
Despite their potential importance with regard to tobacco-related health outcomes, as well as their hypothesized role in the production of tobacco-specific N-nitrosamines, bacterial constituents of tobacco products lack characterization. Specifically, to our knowledge, there has been no comprehensive characterization of the effects of storage conditions on the bacterial communities associated with little cigars and cigarillos. To address this knowledge gap, we characterized the bacterial community composition of the tobacco and wrapper components of the following four products: Swisher Sweets Original; Swisher Sweets, Sweet Cherry; Cheyenne Cigars Full Flavor 100’s; and Cheyenne Menthol Box. Each product was stored under three different conditions of temperature and relative humidity to mimic different user storage conditions: room (20°C 50% RH), refrigerator (5°C 18% RH) and pocket (25°C 30% RH). On days 0, 5, 9 and 14, subsamples were collected, the wrapper and tobacco were separated, and their total DNA was extracted separately and purified. Resulting DNA was then used in PCR assays targeting the V3V4 region of the bacterial 16S rRNA gene, followed by sequencing using Illumina HiSeq 300bp PE. Resulting sequences were processed using the Quantitative Insights Into Microbial Ecology (QIIME) software package, followed by analyses in R using the Phyloseq and Vegan packages. A single bacterial phylum, Firmicutes, dominated in the wrapper subsamples whereas the tobacco subsamples were dominated by Proteobacteria. Cheyenne Menthol Box (CMB) samples were characterized by significant differential abundances for 23 bacterial operational taxonomic units (OTUs) in tobacco subsamples and 27 OTUs in the wrapper subsamples between day 0 and day 14 under all conditions. OTUs from the genera Acinetobacter and Bacillus significantly increased in the CMB tobacco subsamples, and OTUs from Bacillus, Streptococcus, Lactobacillus and Enterococcus significantly increased in the CMB wrapper subsamples over time. These initial results suggest that the bacterial communities of little cigars and cigarillos are dynamic over time and varying storage conditions.